Evaluation of calcium carbonate (CaCO3) inclusion in solid-state kinetic fermentation of Solanum tuberosum postharvest waste - Borras, Luis Miguel; Rodríguez, Carlos Eduardo; Rodríguez, Ángela (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
The objective of this study was to evaluate the pH behavior with CaCO3 inclusions in solid state fermentation of Solanum tuberosum postharvest waste inoculated with a microbial preparation. A supplement was obtained that can be used in animal feed with the following conditions: 89% S. tuberosum, 5% fibrous material (wheat bran); 2% molasses, 1% urea; 2% of the microbial preparation (developed in the research), 0.5% premixed mineral and 0.5% of sodium sulphate. Four treatments were evaluated with 0, 0.25, 0.50 and 0.75% inclusion of CaCO3 to the above mixture at different temperatures (20 and 25ºC), and incubated at different fermentation times (24 and 48 hours). Analysis of variance was carried out according to a completely randomized design with a factorial arrangement (2×2×4) where the factors were two temperatures 20 and 25ºC, two fermentation times 24 and 48 hours and four inclusion levels of calcium carbonate and three replications. A Duncan test was applied for P≤0.05 when necessary. The INFOSTAT statistical package, version 2012, was used for the analysis. The influence of calcium carbonate on pH and MS (P<0.0001) was observed in the study. The pH increased as the percentage of CaCO3 addition supplied for both incubation temperatures increased for 48 hours, according to the values obtained in the fermentation kinetics, with the exception of 25ºC in the highest inclusion level (0.75%). For the DM, an increase in the different inclusion levels of calcium carbonate was observed at a temperature of 20ºC during fermentation although the highest value reached 39.66%. The two protein indicators showed differences for all levels of carbonate inclusion with respect to time and temperatures. However, the crude protein levels were maintained in comparison with those in the microbial preparation, obtaining the highest value with the inclusion of 0.50% CaCO3 at 20ºC, with a marked difference with protein tenors at 25ºC, which were always below the fermentation percentage at 20ºC. The best inclusion of CaCO3 in the fermentation of the postharvest waste of Solanum tuberosum with the microbial preparation was 0.50% at 20ºC, which resulted in an adequate growth of the BAL microorganisms, as reflected in the protein increase.